Preparation and Upconversion Photoluminescence of Er3+/Yb3+ Co-Doped CaWO4 Particles via Microwave-Assisted Metathetic Route - Sung Lim, Chang (Asian Journal of Chemistry, 2013)
Upconversion photoluminescence of Er3+ doped CaWO4 (CaWO4:Er3+) and Er3+/Yb3+ co-doped CaWO4 (CaWO4:Er3+/Yb3+) particles was successfully achieved by a cyclic microwave-assisted metathetic route. Well-crystallized CaWO4:Er3+ and CaWO4:Er3+/Yb3+ particles formed after heat-treatment at 600 ºC for 3 h showed a fine and homogeneous morphology with particle sizes of 1-3 μm. At excitation at 980 nm, CaWO4:Er3+ and CaWO4:Er3+/Yb3+ particles exhibited a strong 525-nm emission band and a weak 550-nm emission band in the green region. The upconversion intensity of CaWO4:Er3+/Yb3+ particles was much higher than that of the CaWO4:Er3+ particles. The Raman spectra of the CaWO4:Er3+/Yb3+ particles indicated the detection of additional peaks at higher frequencies (620, 573, 481, 371 and 355 cm-1) and lower frequencies (315, 265, 217 and 203 cm-1).